Predicting and understanding ecosystem responses to climate change at continental scales. Issue 5 (1st June 2008) - Marshall, John D; Blair, John M; Peters, Debra PC; Okin, Greg; Rango, Albert; Williams, Mark
Abstract : Climate is changing across a range of scales, from local to global, but ecological consequences remain difficult to understand and predict. Such projections are complicated by change in the connectivity of resources, particularly water, nutrients, and propagules, that influences the way ecological responses scale from local to regional and from regional to continental. This paper describes ecological responses to expected changes in four key meso‐scale drivers that influence the ecosystems of the North American continental interior: drought, warming, snowpack disappearance, and altered fire regimes. Changes in these drivers will affect, for example, atmospheric smoke, dust, and reactive nitrogen concentrations; stream discharge; nitrate concentrations; sediment loads; and the vector‐borne spread of invasive species and infectious diseases. A continental network of sensors and simulation models is required to detect changes in the transport vectors – atmospheric, hydrologic, and mechanized –that connect spatial scales. Knowledge of these downwind, downstream, and down‐corridor effects will be critical if we are to understand and forecast responses to climate change at regional to continental scales.